Optimising parcel deliveries in London using dual-mode routing. Issue 6 (3rd June 2019) - Nguyê˜n, Thu Ba T.; Bektaş, Tolga; Cherrett, Tom J.; McLeod, Fraser N.; Allen, Julian; Bates, Oliver; Piotrowska, Marzena; Piecyk, Maja; Friday, Adrian; Wise, Sarah
Abstract: Last-mile delivery operations are complex, and the conventional way of using a single mode of delivery (e.g. driving) is not necessarily an efficient strategy. This paper describes a two-level parcel distribution model that combines walking and driving for a single driver. The model aims to minimise the total travelling time by scheduling a vehicle's routing and the driver's walking sequence when making deliveries, taking decisions on parking locations into consideration. The model is a variant of the Clustered Travelling Salesman Problem with Time Windows, in which the sequence of visits within each cluster is required to form a closed tour. When applied to a case study of an actual vehicle round from a parcel carrier operating in London, savings of over 20% in the total operation time were returned over the current situation where 144 parcels were being delivered to 57 delivery locations.